The Rate of Interest and the Laws of Distribution - Webb, Sidney (Quarterly Journal of Economics, 1888)
The Rate of Interest and the Laws of Distribution Get access Sidney Webb Sidney Webb Lecturer on Economics at the City of London College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 2, Issue 2, January 1888, Pages 188–208, https://doi.org/10.2307/1879488 Published: 01 January 1888